Endovascular treatment of pulmonary arteriovenous malformations in hereditary haemorrhagic telangiectasia (Swiss Medical Weekly, 2015)
PRINCIPLES: To assess the efficiency and complication rates of vaso-occlusion of pulmonary arteriovenous malformations (PAVMs) in Rendu-Osler-Weber disease (hereditary haemorrhagic telangectasia; HHT). METHODS: Seventy-two patients were investigated in our institution for HHT between March 2000 and November 2011. Sixteen presented PAVMs (22.2%), and 11 (68.8%) were treated with vaso-occlusion for a total of 18 procedures. Procedures included coils, plugs and combined approaches. Immediate success and recurrence rate, complication were recorded, as well as persistent and new PAVMs during clinical and computed tomography (CT) follow-up. RESULTS: Eighteen procedures were performed and a total of 37 PAVMs were treated, 19 with coils, 16 with plugs and 2 with combined treatment. Mean CT follow-up time was 41 months (1‒164). No major complication was observed. One distal translocation was treated during the same intervention. Two PAVMs persisted after treatment (5.7%), both treated by means of plug embolisation. One new PAVM was observed during follow-up CT. PAVMs with an afferent artery of less than 3mm or asymptomatic PAVMs were not treated. CONCLUSION: Recent studies have demonstrated that vaso-occlusion has become the gold standard treatment for PAVM. This study is in accordance with previous results and shows a minimal complication rate and little recurrence, whether by coils, plugs, or combined treatments.